PERTANGGUNG JAWABAN PIDANA BAGI PELAKU KEJAHATAN PROSTITUSI TERHADAP ANAK MELALUI TRANSAKSI ELEKTRONIK DITINJAU DARI UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI TRANSAKSI DAN ELEKTRONIK - NOVITA BAIDURI (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT In the era of globalization and free trade as it is today, many emerging various products and / or services marketed to consumers in Indonesia, if not careful in choosing products and / or services consumers want, then consumers will only be objects of exploitation from irresponsible business actors, because unwittingly consumers only take for granted goods and / or services consumed. While food is a commodity that has a high risk because the food is consumed by the community for its survival. But in practice, the trade of food products shows that there are still many business actors who deliberately sell food products that have expired, it is very harmful from consumer rights because it can endanger the health and safety of consumers. Based on the condition of the circulation of food, it can be formulated some of the problems as follows: how the regulation of consumer protection on the distribution of expired food and problems faced by consumers in consuming expired food, and how the form of legal protection against food consumers expired and coaching and supervision of government and agencies which is related to the circulation of expired food, and how the business actors account for the expiration of expired food and consumer dispute resolution mechanisms that can be taken to resolve various violations.